PEMBINAAN ORANG TUA DALAM MENGHADAPI PERILAKU ANAK YANG MENYIMPANG (STUDI DI DESA BUNGA TANJUNG MUKOMUKO BENGKULU) - Yanto - (Professional: Jurnal Komunikasi dan Administrasi Publik, 2015)
The background ofthis studywas the high number of children in primary school age diddeviant behavior, especially in Bunga Tanjung village, Mukomuko, Bengkulu. This phenomenon occured because of the bandwagon attitude were present in children which they adopted from their surrounding environment. Unfortunately adults didn’t realize that their attitudes and behavior which imitated by children could be fatal to the development of their behavior later in life. Ironically, most parents, educators, and community leaders had not paid serious attention to this issue. Based on the above phenomen on writer interested in studying further the issues of children’s deviant behavior and ways taken by parents to deal with children with deviant behaviorin the review of Transactional and Behavioral Analysis. This is afield research which apllied qualitative descriptive analysis method to accurately explain the phenomen on that was found inthe field which critically analyzed and described innarrative from 34 informants who were taken by using snowball sampling technique. The results showed in terms of Transactional, parents used ago state, complementary dan stimulus hunger and strokes. In terms of Behavioral Analysis, parents used operan conditional, imitative learning, giving reward and punishment, reinforsing incompatible behaviours, and operan habituation.Keywords: Edification, Parents Deviant Behavior